Ictal Occurrence of High-Frequency Oscillations Correlates With Seizure Severity in a Rat Model of Temporal Lobe Epilepsy - Birk, Nadja; Schönberger, Jan; Somerlik-Fuchs, Karin Helene; Schulze-Bonhage, Andreas; Jacobs, Julia (Frontiers in Human Neuroscience, 2021)
High frequency oscillations (HFO, ripples 80-250 Hz, fast ripples 250-500 Hz) are biomarkers of epileptic tissue. They are most commonly observed over areas generating seizures and increase in occurrence during the ictal compared to the interictal period. It has been hypothesized that their rate correlates with the severity of epilepsy and seizure in affected individuals. In the present study it was aimed to investigate whether HFO count mirrors the observed behavioral seizure severity using a kainate rat model for temporal lobe epilepsy. Seizures were selected during the chronic epilepsy phase of this model and classified by behavioral severity according to the Racine scale. Seizures with Racine scale 5&6 were considered generalized and severe. HFO were marked in 24 seizures during a preictal, ictal and postictal EEG segment. Duration covered by HFO during these different segments was analyzed and compared between mild and severe seizures. HFO were significantly increased during ictal periods (p<0.001) and significantly decreased during postictal periods (p< 0.03) compared to the ictal segment. Ictal ripples (p=0.04) as well as fast ripples (p=0.02) were significantly higher in severe seizures compared to mild seizures. The present study demonstrates that ictal HFO occurrence mirrors seizure severity in a chronic focal epilepsy model in rats. This is similar to recent observations in patients with refractory mesio-temporal lobe epilepsy. Moreover, postictal HFO decrease might reflect postictal inhibition of epileptic activity. Overall results provide additional evidence that HFO can be used as biomarkers for measuring seizure severity in epilepsy.